Management Of Facilities And Infrastructure In Education Quality Development: A Case Study At Al-Munawwir Islamic Boarding School - Rohmaniyyah, Ummi Alfiyyatur; Susanti, Elina (Proceeding International Conference on Religion, Science and Education, 2025)
The influence of facilities and infrastructure management on the quality of education in schools is very significant. Adequate and well-maintained educational facilities and infrastructure have a positive impact on the smoothness of the learning process as a result the quality of education in schools will increase. The purpose of this study was to determine and describe how the planning, procurement, organization, and use of facilities and infrastructure in improving the quality of education at Al-Munawwir Islamic boarding school. This research was conducted at Al-Munawwir Islamic boarding school using a descriptive qualitative approach. Data sources were obtained through observation, interviews and documentation. Data analysis was carried out by reviewing the data obtained during the data collection process and presenting the data and then drawing conclusions. The data validity technique uses triangulation techniques. The results showed that Al-Munawwir Islamic boarding school has implemented facilities and infrastructure management with steps, namely planning through annual program meetings then organizing with the procurement of facilities and infrastructure, monitoring is carried out by the head of the facilities and infrastructure section to control, repair and remove facilities and infrastructure that do not meet standards, as for maintenance, namely maintenance of infrastructure facilities that have been made available by all boarders. However, there are obstacles such as irregular inventory recording because it is carried out when there is a need, the discovery of facilities that are no longer suitable for use but are still used in activities, and the need for additional facilities and infrastructure at Al-Munawwir Islamic boarding school. It’s hoped that this research can be used as a reference material by Islamic boarding schools to pay more attention to the management of facilities and infrastructure, so that the better the management, the higher the quality of education and produce quality human resources in the future.